2017
DOI: 10.1016/j.fertnstert.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Admixture mapping of uterine fibroid size and number in African American women

Abstract: Objective To evaluate the relationship between genetic ancestry and uterine fibroid characteristics. Design Cross-sectional study. Setting Not applicable. Patient(s) A total of six hundred and nine African American (AA) participants with image- or surgery-confirmed fibroids in the biorepository at Vanderbilt University (BioVU) electronic health record biorepository and the Coronary Artery Risk Development in Young Adults (CARDIA) studies were included. Intervention(s) None Main outcome Measure(s) Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Further supporting this are ndings from our group that demonstrated that the frequency of broproliferative risk alleles varies by geographic ancestry with a much higher burden among African-ancestry populations and lower among European-derived populations (Hellwege et al, 2017). Admixture mapping analysis of broid risk and multiple broid risk also demonstrates increased risk among Black women compared to White women (Bray et al, 2017, Giri et al, 2017.…”
Section: Introductionsupporting
confidence: 64%
“…Further supporting this are ndings from our group that demonstrated that the frequency of broproliferative risk alleles varies by geographic ancestry with a much higher burden among African-ancestry populations and lower among European-derived populations (Hellwege et al, 2017). Admixture mapping analysis of broid risk and multiple broid risk also demonstrates increased risk among Black women compared to White women (Bray et al, 2017, Giri et al, 2017.…”
Section: Introductionsupporting
confidence: 64%
“…Our finding that black Veterans with UF were more likely than white Veterans with UF to have larger uterine size is consistent with prior literature. 41 Previously, Kjerulff et al reported that, compared with white women undergoing hysterectomy for UF, black women had ∼100 g larger mean postoperative uterine weight (420.8 g vs. 319.1 g). 42 Prospective data also indicate that black people experience earlier onset of fibroids and larger and more numerous fibroids than their white counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…However, these differences in UF cannot be explained by genetic variations in socially constructed racial categories. 41 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, so-called “protective” single-nucleotide variants, which reduce UL risk, have been discovered in the introns of the following genes: KCNMB2 (potassium calcium-activated channel subfamily M regulatory beta subunit 2), FBN2 (fibrillin 2), ESR1 (oestrogen receptor 1) and CELF4 (CUGBP Elav-like family member 4) [ 82 ]. Researchers have also described COL6A3 (collagen type VI alpha 3 chain), COL13A (collagen type XIII alpha 1 chain), ARHGAP26 (Rho GTPase activating protein 26), MAN1C1 (mannosidase alpha class 1C member 1), BET1L (Bet1 golgi vesicular membrane trafficking protein like), TNRC6B (trinucleotide repeat containing adaptor 6B) and COMT (catechol-O-methyltransferase) gene variants associated with the accumulation of ECM in the UL tissue, the size, localisation and the multiple form of UL [ 83 , 84 , 85 , 86 , 87 ].…”
Section: The Role Of Woman’s Genotype In Ul Aetiologymentioning
confidence: 99%